2019
DOI: 10.1016/j.apcatb.2018.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Synergism between non-thermal plasma and photocatalysis: Implicationsin the post discharge of ozone at a pilot scale in a catalytic fixed-bed reactor

Abstract: HIGHLIGHTS  C4H8O removal using (UV-TiO2/plasma) + catalytic-bed system is studied.  Specific catalysts are tested for C4H8O/O3 removal at pilot scale.  Impacts of operating parameters on process performance are defined.  Highly efficient synergetic association was obtained.  Better performance in mineralization rate via ozone valorization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…For this reason, technologies that have the ability to purify air from organic contaminants with efficient and inexpensive processes became the objective of many research groups [5,6]. Thus, several remediation techniques were used to reduce this kind of pollutants using photocatalysts [7,8], non-thermal plasma [9,10], catalytic ozonation [11]. Scientific studies on photocatalysis started about four decades ago and showed that photocatalysis can be an interesting technique for environmental remediation [7,8,12].…”
Section: -Introductionmentioning
confidence: 99%
“…For this reason, technologies that have the ability to purify air from organic contaminants with efficient and inexpensive processes became the objective of many research groups [5,6]. Thus, several remediation techniques were used to reduce this kind of pollutants using photocatalysts [7,8], non-thermal plasma [9,10], catalytic ozonation [11]. Scientific studies on photocatalysis started about four decades ago and showed that photocatalysis can be an interesting technique for environmental remediation [7,8,12].…”
Section: -Introductionmentioning
confidence: 99%
“…Some GC material could act as a catalyst, as it was already observed for metal oxides, zeolites and carbon-based materials which can enhance the ozone-oxidation of VOCs (Brodu et al, 2012;Kastner et al, 2008;Masuda et al, 2001;Oyama, 2000). On the surface of these catalysts, the ozone reacts with the active sites (Lewis acid site) to form secondary oxidizing agents (atomic oxygen, peroxide ions, hydroxyl radicals), which subsequently react with the pollutants (Abou Saoud et al, 2019;Brodu et al, 2018;Wang et al, 2018).…”
Section: Varying Gc Parametersmentioning
confidence: 98%
“…Volatile organic compounds (VOCs) contribute to the formation of pollutants such as photochemical smog and ozone in the atmosphere . In addition, long-term exposure to VOCs can pose a threat to human health, including headaches, damage to the respiratory system and nervous system, , and in severe cases, increase the risk of cancer . Therefore, it is very important to take effective measures to remove VOCs in the environment and minimize the threats to environment and human health.…”
Section: Introductionmentioning
confidence: 99%